Removal of chromium (cr) and copper (cu) from domestic wastewater using eggshells waste as adsorbent with multi variable dose and contact time - Baharudin, Fauzi; Ali Abas, Ain Azreena; Kassim, Jalina; Mohd Imran, Siti Nurulhuda; Ghazali, Suriati (Universiti Teknologi MARA (UiTM), 2024)
The removal of Chromium (Cr) and Copper (Cu) from domestic wastewater was investigated using eggshell waste as an adsorbent. The objective of this research was to evaluate the efficacy of eggshell waste in removing these heavy metals and to determine the most optimal conditions for maximum removal efficiency. Adsorption experiments were carried out using the highest values tested, with an adsorbent dosage of 1.5 g and a contact time of 60 minutes. The results showed that both Chromium and Copper removal were promising. The removal efficiency for Chromium was found to be 69.94% at a dosage of 1.5 g, while Copper had a higher removal efficiency of 84.62%. These results highlight the potential of eggshell waste as an effective adsorbent for heavy metal removal from domestic wastewater. Furthermore, an examination of contact time revealed that longer durations significantly enhanced removal efficiencies. Chromium had a removal efficiency of 65.90% at the longest contact time of 60 minutes, while Copper had an impressive removal efficiency of 84.62%. These findings highlight the importance of allowing enough contact time for heavy metal adsorption. The high removal efficiencies at the specified adsorbent dosage and contact time show that eggshell waste has the potential to be a cost-effective and sustainable solution for heavy metal removal in domestic wastewater treatment systems.